Novel procaine-based gemini zwitterion incorporated PVDF membranes for efficient treatment of oily wastewater. Issue 3 (June 2022) - Mansha, Muhammad; Salhi, Billel; Ali, Shahid; Khan, Safyan A.; Baig, Nadeem
Abstract: Oily wastewater treatment has great significance due to environmental and industrial perspectives. Oily wastewater has emerged as one of the leading causes of water contamination. Owing to the lower efficiencies of the conventional methods, membrane technology is an emerging solution for separating the stabilized oil contaminants from water. In this work, a novel procaine-based zwitterionic geminal surfactant (PZGS ) i.e., 3, 3′-((((4, 4′-(decanedioylbis(azanediyl)) bis(benzoyl))bis(oxy)) bis(ethane-2, 1-diyl)) bis(diethylammoniumdiyl)) bis(propane-1-sulfonate) synthesized by utilizing procaine hydrochloride and 1, 3-propane sultone precursors. The PZGS was well-characterized by 1 H NMR, 13 C NMR, and FTIR spectroscopy. The synthesized PZGS was utilized to fabricate procaine-based zwitterionic gemini surfactant incorporated PVDF membranes (PZGS-Mx -PVDF), and the membranes were thoroughly investigated by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), and contact angle goniometry. It is observed that the performance of these newly fabricated membranes (PZGS-Mx -PVDF) was significantly improved after incorporating PZGS into the PVDF membranes. The surface of membranes has become water-friendly as the water contact angle substantially changed from 84.1° to 58.1°. In controlled addition of PZGS, the PZGS-M2 -PVDF membrane has shown a substantially improved flux of 4.5 times to pristine PVDF. The maximum oil rejection of > 99.3% was attained using the PZGS-M1 -PVDF membrane. A high flux recovery ratio (FRR) of about 83% was observed with the PZGS-M2 -PVDF membrane. The PZGS-Mx -PVDF membranes have shown a good flux recovery ratio after continuous use of oil-in-water emulsions. The excellent separation efficiency, high permeation flux, and good flux recovery ratio indicated that the introduced PZGS-Mx -PVDF membranes have a significant potential for oily wastewater treatment. Graphical Abstract: ga1 Highlights: Procaine-based gemini zwitterion PVDF membranes fabricated by the phase inversion process. Incorporation of gemini zwitterion improved the hydrophilicity and antifouling behavior of the PVDF membrane. Procaine-based gemini zwitterion incorporated PVDF membrane has shown excellent rejection of 99.3%. The modified PVDF has shown an excellent flux recovery ratio greater than 80%.